The Influence Of Easy Business Licensing Through The Implementation Of Online Single Submission (OSS) Applications On Increasing Investment In North Sumatra Province (Mid Large Scale Industrial Sector) - Maharani Saragih, Desni; Sabrina, T.; Purwoko, Agus (Publisher Cv. Inara, 2024)
The government issued the latest policy related to investment, namely Government Regulation Number 5 of 2021 which regulates Online Single Submission (OSS) and Government Regulation Number 6 of 2021. However, investment in the industrial sector in North Sumatra Province in fact it did not show an increase after the implementation of the application in 2018. In contrast to Indonesia's EoDB ranking, which after the implementation of the Online Single Submission (OSS) application in 2018 from rank 91 crawled up to rank 72. So the purpose of this study is to analyze the effect of ease of licensing trying through the implementation of the Online Single Submission Application to increase investment in the industrial sector in North Sumatra Province. The research method used is a quantitative approach by collecting data in the form of numbers from a Likert scale questionnaire. The sample used was 80 respondents using the non-probability sampling technique using purposive sampling method. Data analysis used validity tests, reliability tests, and path analysis (Path Analysis) with the aim of knowing the direct and indirect effects of the ease of business licensing variables through the implementation of the Online Single Submission Application on increasing investment. From the results of the study that the ease of licensing tries to influence directly or indirectly through the implementation of the Online Single Submission application on increasing investment in the category that is still less effective and the results of calculating direct effect is 41,5% and indirect effect is 46,45%. Where there are two policy indicators, transparency indicators for domestic investment and Accountability for foreign investment do not have a significant direct effect and coordination indicators provide a direct and significant influence on domestic investment and foreign investment.